Representasi Standar Perempuan Cantik dalam Iklan Perawatan Rambut L'oreal di Tiktok - Radika Dava Praditya; Yermanida Hayyatun Nufus; Fajar Junaedi; Farchan Jelani (ANALOGI Jurnal Ilmu Sosial dan Humaniora, 2026)
This advertisement features a representation of straight hair as the ideal hair for women. Advertisements often promote certain beauty standards, particularly by idealizing straight hair as a characteristic of the "perfect" woman. In society, women who are considered ideal are usually depicted with straight hair, fair skin, smooth complexion, and slim bodies. This representation creates a narrow beauty stereotype, pressuring women to conform to these standards in order to be accepted or considered attractive. This advertisement features the representation of straight hair as the ideal hair for women. Advertisements often promote certain beauty standards, particularly by idealizing straight hair as a characteristic of the "perfect" woman. In society, women who are considered ideal are usually depicted with straight hair, fair skin, smooth complexion, and slim bodies. This representation creates a narrow beauty stereotype, pressuring women to conform to these standards in order to be accepted or considered attractive. In this study, it was found that straight and neat hair for women is something that many women idolize. Meanwhile, in Indonesia, there are distinctive hair shapes that vary in each region.